Types of Personal Changes of Future Specialists, Psychologists-Psychotherapists - Yavorska, Аnastasiya (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. Socio-political processes exacerbated the problems of psychological assistance to citizens; training of qualified psychologists-therapists. One of the factors of a specialist's personality is the ability for personal change. The goal is to reveal the content of the main factors of personal changes of future psychologists-therapistsMethods. The research used the "Big Five" methods; Herzberg's test; "Diagnostics of socio-psychological personality attitudes" (O. Potemkina); "Value questionnaire" (Sh. Schwartz); "Research of volitional self-regulation" (A. Zverkov, E. Eidman); "Diagnostics of motivational orientations in interpersonal communications" (I. Ladanov, V. Urazaeva); "Motivation of professional activity" (K. Zamfir); "Test of social intelligence" (J. Gilford); "Self-Assessment Questionnaire" (V. Stolin, S. Pantileev); "Scale of psychological well-being" (K. Riff) - separate scales from which factors of personal changes were included.Results. As a result of factor analysis using the method of principal components, four factors of personal changes of future psychologists- therapists were identified: 1) "pattern" - tendency to change, voluntary self-control, responsibility, ability to achieve personal success, openness to experience, orientation to the process, independence, universalism, inner type motivation and general self-regulation, social thinking, psychological well-being; 2) "personal-purpose" - social recognition, achievement of personal success, content of work, orientation to results, power, compromise; hedonism, self-control, internal and external positive motivation, self-acceptance; 3) "professional-purpose" - pleasantness, cooperation, work content, process orientation, money; selfishness, kindness, external positive and negative motivation; 4) "pragmatic-humanistic" - extraversion, neuroticism, cooperation, altruism, independence, security, orientation towards acceptance of others, positive relationships.Сonclusion. The process of unfolding individual personal states and traits is the development of the personality, therefore personal changes are the development of the personality. The concept of personal change (personal changes) is generic to the concept of personality development, since the latter involves the specification of personal formations according to the criteria of their complexity and specification, therefore the concepts of change and personality change are different.
Keywords: personal changes; the concept of change; the future psychotherapist; typological groups of specialists; criteria for group typology; types of personal changes; the problem of the specialist's personality